It Just Makes Sense: Keeping Sensory Devices With Surgical Patients - Prystenski, Jaime; Nowak, Heather; Barber, Lance (Operating Room Nurses Association of Canada Journal, 2017)
Operating room staff can develop simple strategies that significantly improve the patient’s perspective on the perioperative experience. Research has shown the importance of sensory devices in minimizing the risk of post-operative delirium and confusion. Change management tools, such as Lean methodology, had, in 2008, become a critical component in improving organizational excellence to provide quality care at St. Boniface Hospital in Winnipeg, MB. Some of the Lean tools and strategies include the A3 framework which, along with the Rapid Improvement Events and the concept of Plan, Do, Study, Act/Adjust (PDSA), help facilitate rapid change. In 2008 St. Boniface Hospital embarked on a transformative journey to utilizing practices developed based on Lean methodology.1 The Surgery Program was one of the first two programs to participate and continues to be involved today. The purpose of this review is to provide an analysis of how Lean A3 change initiatives can improve patient access to their sensory device(s), throughout their surgical experience, as a means of enhancing their care, comprehension, and perioperative recovery while minimizing post-operative complications such as post-op delirium. Discussion includes, a description of the sensory device issues and relevant challenges, and the influence of Lean strategizing on the project.1 Method: Comprised a Lean A3 planning strategy and a Rapid Improvement Event involving direct care staff in the brain-storming processes and in the planning for change.1 Anecdotal information was collected from previous patients and patients involved in the project’s test days. A control group was not available for comparison. Results: Staff understood the rationale behind the change process and patients and families were satisfied by the quick access to sensory devices in the postanesthesia recovery room. Conclusion: Research has shown the importance of sensory devices in minimizing the risk of post-operative delirium and confusion. Changes in the pre-operative area and in work processes enhance the patient’s perception and comprehension throughout their surgical experience, as explained by anecdotal results.